Keywords in creative writing - Bishop, Wendy, author; Starkey, David, author; Utah State University Press, publisher (Colorado State University. Libraries, 2006)
Wendy Bishop and David Starkey have created a remarkable resource volume for creative writing students and other writers just getting started. In two- to ten-page discussions, these authors introduce forty-one central concepts in the fields of creative writing and writing instruction, with discussions that are accessible yet grounded in scholarship and years of experience. Keywords in Creative Writing provides a brief but comprehensive introduction to the field of creative writing through its landmark terms, exploring concerns as abstract as postmodernism and identity politics alongside very practical interests of beginning writers, like contests, agents, and royalties. This approach makes the book ideal for the college classroom, and unique in the field, combining the pragmatic accessibility of popular writer's handbooks, with a wider, more scholarly vision of theory and research.--Provided by publisher.
Adjunct and temporary faculty -- Agents -- Anthology -- Associated writing programs -- Author -- Block and procrastination -- Chapbooks -- Collaboration -- Composition -- Conferences, colonies, and residencies -- Contests -- Contributor's copy -- Copyright and intellectual property -- Creative dissertation -- Creative nonfiction -- Creativity -- Editors and publishers -- Electronic literature -- Fiction -- Genre -- Grants -- Identity politics -- Image and metaphor -- MFA (master of fine arts) -- Pedagogy -- Poetry -- Postmodernism -- Reading -- Rejection -- Royalties and permission fees -- Schmoozing -- Scriptwriting -- Style and voice -- Submissions -- Teaching jobs -- Theory.
Keywords: English language -- Rhetoric -- Study and teaching -- Terminology; Creative writing -- Study and teaching -- Terminology; English language -- Rhetoric -- Terminology; Creative writing -- Terminology